Converse nonimplication

Logical connective
Venn diagram of P Q {\displaystyle P\nleftarrow Q}
(the red area is true)

In logic, converse nonimplication[1] is a logical connective which is the negation of converse implication (equivalently, the negation of the converse of implication).

Definition

Converse nonimplication is notated P Q {\displaystyle P\nleftarrow Q} , or P Q {\displaystyle P\not \subset Q} , and is logically equivalent to ¬ ( P Q ) {\displaystyle \neg (P\leftarrow Q)} and ¬ P Q {\displaystyle \neg P\wedge Q} .

Truth table

The truth table of A B {\displaystyle A\nleftarrow B} .[2]

A {\displaystyle A} B {\displaystyle B} A B {\displaystyle A\nleftarrow B}
FFF
FTT
TFF
TTF

Notation

Converse nonimplication is notated p q {\textstyle p\nleftarrow q} , which is the left arrow from converse implication ( {\textstyle \leftarrow } ), negated with a stroke (/).

Alternatives include

  • p q {\textstyle p\not \subset q} , which combines converse implication's {\displaystyle \subset } , negated with a stroke (/).
  • p ~ q {\textstyle p{\tilde {\leftarrow }}q} , which combines converse implication's left arrow ( {\textstyle \leftarrow } ) with negation's tilde ( {\textstyle \sim } ).
  • Mpq, in Bocheński notation

Properties

falsehood-preserving: The interpretation under which all variables are assigned a truth value of 'false' produces a truth value of 'false' as a result of converse nonimplication

Natural language

Grammatical

Example,

If it rains (P) then I get wet (Q), just because I am wet (Q) does not mean it is raining, in reality I went to a pool party with the co-ed staff, in my clothes (~P) and that is why I am facilitating this lecture in this state (Q).

Rhetorical

Q does not imply P.

Colloquial

Boolean algebra

Converse Nonimplication in a general Boolean algebra is defined as q p = q p {\textstyle q\nleftarrow p=q'p} .

Example of a 2-element Boolean algebra: the 2 elements {0,1} with 0 as zero and 1 as unity element, operators {\textstyle \sim } as complement operator, {\textstyle \vee } as join operator and {\textstyle \wedge } as meet operator, build the Boolean algebra of propositional logic.

x {\textstyle {}\sim x} 1 0
x 0 1
and
y
1 1 1
0 0 1
y x {\textstyle y_{\vee }x} 0 1 x
and
y
1 0 1
0 0 0
y x {\textstyle y_{\wedge }x} 0 1 x
then y x {\displaystyle \scriptstyle {y\nleftarrow x}\!} means
y
1 0 0
0 0 1
y x {\displaystyle \scriptstyle {y\nleftarrow x}\!} 0 1 x
(Negation) (Inclusive or) (And) (Converse nonimplication)

Example of a 4-element Boolean algebra: the 4 divisors {1,2,3,6} of 6 with 1 as zero and 6 as unity element, operators c {\displaystyle \scriptstyle {^{c}}\!} (co-divisor of 6) as complement operator, {\displaystyle \scriptstyle {_{\vee }}\!} (least common multiple) as join operator and {\displaystyle \scriptstyle {_{\wedge }}\!} (greatest common divisor) as meet operator, build a Boolean algebra.

x c {\displaystyle \scriptstyle {x^{c}}\!} 6 3 2 1
x 1 2 3 6
and
y
6 6 6 6 6
3 3 6 3 6
2 2 2 6 6
1 1 2 3 6
y x {\displaystyle \scriptstyle {y_{\vee }x}\!} 1 2 3 6 x
and
y
6 1 2 3 6
3 1 1 3 3
2 1 2 1 2
1 1 1 1 1
y x {\displaystyle \scriptstyle {y_{\wedge }x}} 1 2 3 6 x
then y x {\displaystyle \scriptstyle {y\nleftarrow x}\!} means
y
6 1 1 1 1
3 1 2 1 2
2 1 1 3 3
1 1 2 3 6
y x {\displaystyle \scriptstyle {y\nleftarrow x}\!} 1 2 3 6 x
(Co-divisor 6) (Least common multiple) (Greatest common divisor) (x's greatest divisor coprime with y)

Properties

Non-associative

r ( q p ) = ( r q ) p {\displaystyle r\nleftarrow (q\nleftarrow p)=(r\nleftarrow q)\nleftarrow p} if and only if r p = 0 {\displaystyle rp=0} #s5 (In a two-element Boolean algebra the latter condition is reduced to r = 0 {\displaystyle r=0} or p = 0 {\displaystyle p=0} ). Hence in a nontrivial Boolean algebra Converse Nonimplication is nonassociative.

( r q ) p = r q p (by definition) = ( r q ) p (by definition) = ( r + q ) p (De Morgan's laws) = ( r + r q ) p (Absorption law) = r p + r q p = r p + r ( q p ) (by definition) = r p + r ( q p ) (by definition) {\displaystyle {\begin{aligned}(r\nleftarrow q)\nleftarrow p&=r'q\nleftarrow p&{\text{(by definition)}}\\&=(r'q)'p&{\text{(by definition)}}\\&=(r+q')p&{\text{(De Morgan's laws)}}\\&=(r+r'q')p&{\text{(Absorption law)}}\\&=rp+r'q'p\\&=rp+r'(q\nleftarrow p)&{\text{(by definition)}}\\&=rp+r\nleftarrow (q\nleftarrow p)&{\text{(by definition)}}\\\end{aligned}}}

Clearly, it is associative if and only if r p = 0 {\displaystyle rp=0} .

Non-commutative

  • q p = p q {\displaystyle q\nleftarrow p=p\nleftarrow q} if and only if q = p {\displaystyle q=p} #s6. Hence Converse Nonimplication is noncommutative.

Neutral and absorbing elements

  • 0 is a left neutral element ( 0 p = p {\displaystyle 0\nleftarrow p=p} ) and a right absorbing element ( p 0 = 0 {\displaystyle {p\nleftarrow 0=0}} ).
  • 1 p = 0 {\displaystyle 1\nleftarrow p=0} , p 1 = p {\displaystyle p\nleftarrow 1=p'} , and p p = 0 {\displaystyle p\nleftarrow p=0} .
  • Implication q p {\displaystyle q\rightarrow p} is the dual of converse nonimplication q p {\displaystyle q\nleftarrow p} #s7.

Converse Nonimplication is noncommutative
Step Make use of Resulting in
s.1 Definition q ~ p = q p {\displaystyle \scriptstyle {q{\tilde {\leftarrow }}p=q'p\,}\!}
s.2 Definition p ~ q = p q {\displaystyle \scriptstyle {p{\tilde {\leftarrow }}q=p'q\,}\!}
s.3 s.1 s.2 q ~ p = p ~ q     q p = q p {\displaystyle \scriptstyle {q{\tilde {\leftarrow }}p=p{\tilde {\leftarrow }}q\ \Leftrightarrow \ q'p=qp'\,}\!}
s.4 q {\displaystyle \scriptstyle {q\,}\!} = {\displaystyle \scriptstyle {=\,}\!} q .1 {\displaystyle \scriptstyle {q.1\,}\!}
s.5 s.4.right - expand Unit element = {\displaystyle \scriptstyle {=\,}\!} q . ( p + p ) {\displaystyle \scriptstyle {q.(p+p')\,}\!}
s.6 s.5.right - evaluate expression = {\displaystyle \scriptstyle {=\,}\!} q p + q p {\displaystyle \scriptstyle {qp+qp'\,}\!}
s.7 s.4.left = s.6.right q = q p + q p {\displaystyle \scriptstyle {q=qp+qp'\,}\!}
s.8 q p = q p {\displaystyle \scriptstyle {q'p=qp'\,}\!} {\displaystyle \scriptstyle {\Rightarrow \,}\!} q p + q p = q p + q p {\displaystyle \scriptstyle {qp+qp'=qp+q'p\,}\!}
s.9 s.8 - regroup common factors {\displaystyle \scriptstyle {\Rightarrow \,}\!} q . ( p + p ) = ( q + q ) . p {\displaystyle \scriptstyle {q.(p+p')=(q+q').p\,}\!}
s.10 s.9 - join of complements equals unity {\displaystyle \scriptstyle {\Rightarrow \,}\!} q .1 = 1. p {\displaystyle \scriptstyle {q.1=1.p\,}\!}
s.11 s.10.right - evaluate expression {\displaystyle \scriptstyle {\Rightarrow \,}\!} q = p {\displaystyle \scriptstyle {q=p\,}\!}
s.12 s.8 s.11 q p = q p     q = p {\displaystyle \scriptstyle {q'p=qp'\ \Rightarrow \ q=p\,}\!}
s.13 q = p     q p = q p {\displaystyle \scriptstyle {q=p\ \Rightarrow \ q'p=qp'\,}\!}
s.14 s.12 s.13 q = p     q p = q p {\displaystyle \scriptstyle {q=p\ \Leftrightarrow \ q'p=qp'\,}\!}
s.15 s.3 s.14 q ~ p = p ~ q     q = p {\displaystyle \scriptstyle {q{\tilde {\leftarrow }}p=p{\tilde {\leftarrow }}q\ \Leftrightarrow \ q=p\,}\!}

Implication is the dual of Converse Nonimplication
Step Make use of Resulting in
s.1 Definition dual ( q ~ p ) {\displaystyle \scriptstyle {\operatorname {dual} (q{\tilde {\leftarrow }}p)\,}\!} = {\displaystyle \scriptstyle {=\,}\!} dual ( q p ) {\displaystyle \scriptstyle {\operatorname {dual} (q'p)\,}\!}
s.2 s.1.right - .'s dual is + = {\displaystyle \scriptstyle {=\,}\!} q + p {\displaystyle \scriptstyle {q'+p\,}\!}
s.3 s.2.right - Involution complement = {\displaystyle \scriptstyle {=\,}\!} ( q + p ) {\displaystyle \scriptstyle {(q'+p)''\,}\!}
s.4 s.3.right - De Morgan's laws applied once = {\displaystyle \scriptstyle {=\,}\!} ( q p ) {\displaystyle \scriptstyle {(qp')'\,}\!}
s.5 s.4.right - Commutative law = {\displaystyle \scriptstyle {=\,}\!} ( p q ) {\displaystyle \scriptstyle {(p'q)'\,}\!}
s.6 s.5.right = {\displaystyle \scriptstyle {=\,}\!} ( p ~ q ) {\displaystyle \scriptstyle {(p{\tilde {\leftarrow }}q)'\,}\!}
s.7 s.6.right = {\displaystyle \scriptstyle {=\,}\!} p q {\displaystyle \scriptstyle {p\leftarrow q\,}\!}
s.8 s.7.right = {\displaystyle \scriptstyle {=\,}\!} q p {\displaystyle \scriptstyle {q\rightarrow p\,}\!}
s.9 s.1.left = s.8.right dual ( q ~ p ) = q p {\displaystyle \scriptstyle {\operatorname {dual} (q{\tilde {\leftarrow }}p)=q\rightarrow p\,}\!}

Computer science

An example for converse nonimplication in computer science can be found when performing a right outer join on a set of tables from a database, if records not matching the join-condition from the "left" table are being excluded.[3]

References

  1. ^ Lehtonen, Eero, and Poikonen, J.H.
  2. ^ Knuth 2011, p. 49
  3. ^ "A Visual Explanation of SQL Joins". 11 October 2007. Archived from the original on 15 February 2014. Retrieved 24 March 2013.

External links

  • Media related to Converse nonimplication at Wikimedia Commons
  • v
  • t
  • e
  • Tautology/True  {\displaystyle \top }
Philosophy portal